HIGHER EDUCATION INTERNAL ACADEMIC QUALITY AUDIT INFORMATION SYSTEM - Sudianto, Lande; Simon, Petrus (International Journal of Research -GRANTHAALAYAH, 2020)
University of Christian Indonesian Paulus (UKI Paulus) had started the college quality assurance system by setting the standard, policy and quality of documents. However, it is not supported yet by the information system, which make the process of standard socialization, policy and quality document were not effective and causes limited access to anyone who need the information. Moreover, during the implementation of monitoring and evaluation (monev), quality audits is also inefficient and become a barrier for the implementation of the quality assurance system. Therefore, the information system based on data Internal Academic Quality Audit (Audit MutuAkademik Internal/AMAI) was developed using Unified Modeling Language as part of information and communication technology. The assessment of AMAI of UKI Paulus was carried out by the auditors to every departments by seeing the audited form then count the score of each rubric in order to obtain the standard value and perspective. The system of AMAI provides the report of academic quality assessment from each department to the related leader of the implementation unit. The presence of this system had helped the implementation of quality assurance system for university in order to improve the quality of their institution. The development of information system based on data, AMAI, uses the five stages paradigm of the System Development Life Cycle (SDLC): (1) identification of system requirements; (2) analysis and modeling system; (3) making the system; (4) system assessment and improvement; (5) implementation.